BRIDGING THE GAP: COMMUNITY PARTICIPATION FOR ENHANCED SANITATION ADOPTION AND USAGE - Dr. R Nagarajan (International Journal of Medical Science and Public Health Research, 2024)
This paper examines the critical role of community participation in improving the adoption and sustained usage of sanitation facilities. By engaging local communities in the planning, implementation, and monitoring processes, sanitation projects can address cultural, social, and practical barriers more effectively. Case studies from various regions highlight successful strategies and practices that have led to increased community ownership and long-term commitment to maintaining sanitation infrastructure. The findings underscore the importance of participatory approaches in achieving public health goals and enhancing the overall impact of sanitation initiatives.